The Effect of Grape Cultivar and Yeast Strain on Fermentation Rate and Concentration of Volatile Components in Wine - Houtman, A.C.; du Plessis, C.S. (South African Journal of Enology and Viticulture, 2017)
Wines were made from five grape cultivars using eight strains of Saccharomyces cerevisiae. The mean fermentation rate was determined for the completed fermentation as well as for the yeast proliferation phase. The concentrations of thirty volatile wine components were gas chromatographically determined using a packed column. Fermentation rate and wine volatile production are largely affected by a juice turbidity fraction. It was indicated that cultivar juices differed in the filterability of that fraction in that filtration of Colombar and Chenin blanc juices caused serious lagging fermentation problems whereas the filtrates of Cape Riesling and Muscat d’ Alexandrie juices readily fermented dry. Although seven of the eight yeast strains required the turbidity fraction for active yeast proliferation and completion of fermentation, the requirements of these yeast strains for this fraction differed markedly. Three groups of volatiles could be distinguished in the wines, namely those whose concentrations were: • mainly related to the grape juice, • dependent on precursors in the juice and the chemical transformation capacity of the yeast strain, and • dependent on the yeast strain. A basic fermentation bouquet concept was proposed.